Torque Analysis and Dynamic Performance Improvement of a PMSM for EVs by Skew Angle Optimization - Shi, Zhou; Sun, Xiaodong; Cai, Yingfeng; Yang, Zebin; Lei, Gang; Guo, Youguang; Zhu, Jianguo (IEEE transactions on applied superconductivity, 2019)
In this paper, a permanent magnet synchronous machine (PMSM) for electric vehicles (EVs) is studied. Since EVs need to face some low speed road conditions, it is necessary to drive the machine to maintain a stable torque at low speed. The stator skew slot is often adopted to reduce torque ripple; however, it declines the output torque at same time. Besides, the difference between positive rotation performance and negative rotation performance, which caused by the skew slot are often ignored. Through the finite element analysis, the cogging torque and dynamic performance of the PMSM at different skew angle are studied. Moreover, the different influence of slot skew angle on positive and negative rotation performance is studied. Then, the optimum skew angle of the PMSM is studied through comprehensive consideration. Finally, the cogging torque of the prototype is verified to be less than 2N·m through the experiment.